If You’re Happy, Then You Know It: The Logic of Happiness . . . and Sadness - Azimipour , Sanaz; Naumov, Pavel (Logic and Logical Philosophy, 2024)
The article proposes a formal semantics of happiness and sadness modalities in the imperfect information setting. It shows that these modalities are not definable through each other and gives a sound and complete axiomatization of their properties.